Multi-Ricker Spectral Modeling in the S-transform Domain for Enhancing Vertical Resolution of Seismic Reflection Data - Winardhi, Sonny; Pranowo, Waskito (Geological Agency, 2019)
DOI: 10.17014/ijog.6.3.223-233We present a relatively straightforward methodology for extending seismic bandwidth and hence enhancing the seismic resolution by performing time-variant deconvolution. We use the generalized S-transform (GST) approach in order to properly compute the time-frequency components of the seismic reflection trace. In estimating the time-variant wavelet, we propose a spectral modeling method named multi-Ricker spectral approximation (MRA). After obtaining the estimated wavelet spectrum at each time sample, a deconvolution filter can then be builtÂ and applied in the S-transform domain. This proposed time-variant seismic enhancement method needs neither information on subsurface attenuation model nor assumption that the subsurface reflectivity is random. It is a data-driven methodology which is based on the seismic data only. We validate this proposed method on a synthetic and apply to a field data. Results show that, after enhancement, overall seismic bandwidth can be extended resulting in higher vertical resolution. Correlation with VSP corridor stack at well location ensures that the generated reflection details after enhancement is geologically plausible.